The recovery of the former University pediatric clinics in Cagliari: a project for the reuse, environmental redevelopment and structural and anti-seismic retrofitting of a modern building in a monumental centre - Carlo Atzeni; Stefano Cadoni; Luigi Fenu; Francesco Marras; Paolo Putzulu; Francesco Sedda; Claudio Sirigu (Tema, 2018)
Glass block is a building product widely used for the construction of translucent buildingfaçades and roofs. The need to adapt the product to the regulations in the field of energy saving and environmental sustainability has led to the design of innovative configurations, through theintegration of different sub-components. These ones are able to improve its energy performanceby means of the integration of a “thermal belt”, cold glued to the glass shells, which constitute the traditional glass block, and 3rd generation solar cells. This paper reports the first results ofthe experimental program designed to assess some durability components: inherent and critical reliability.